Conscientiousness and Affective Commitment: The Mediating Role of Job Satisfaction - Putri, Aisyah; Trinanda, Okki (Human Resource Management Studies, 2024)
This research aims to describe the influence of conscientiousness on affective commitment at the employees PT Pos Indonesia KCU Padang with job satisfaction as a mediating variable. This research is quantitative research. This exploratory research is causal research. The population in the study were all employees of PT Pos Indonesia KCU Padang, totaling 86 people. Meanwhile, the number of samples used in this research was determined using total sampling so that the sample size was the same as the population, namely 86 people. Collect information using a Likert scale. The analysis technique used is SmartPLS 4 software. The research results show that: (1) Conscientiousness has a positive and significant effect on affective commitment in PT Pos Indonesia KCU Padang employees. (2) Conscientiousness has a positive and significant effect on job satisfaction in PT Pos Indonesia KCU Padang employees. (3) Job satisfaction has a positive and significant effect on affective commitmen in PT Pos Indonesia KCU Padang employees. (4) Conscientiousness has a positive and significant effect on affective commitment with job satisfaction as a mediating variable in the PT Pos Indonesia KCU Padang employees.